2018
DOI: 10.1016/j.jcrc.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of traditional microbiological culture and 16S polymerase chain reaction analyses for identification of preoperative airway colonization for patients undergoing lung resection

Abstract: Rates of colonization identified by culture and 16S PCR analyses of BAL samples were similar. Future research should attempt to clarify associations between airway colonization identified by 16S PCR and outcomes. 16S PCR may be useful when stratifying risk of postoperative respiratory complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…In 7 of the cases where different www.nature.com/scientificreports www.nature.com/scientificreports/ predominant organisms were identified, NGS16S identified anaerobes (Table 5), consistent with the fact that anaerobes are not routinely cultured for this specimen type. Prevotella and Veillonella were frequently recovered (14/20 samples, Table 3) and represented the most abundant CRC in 6/20 samples (Table 5), consistent with previous studies 14,[25][26][27] . Anaerobes were the predominant organism in approximately one third of the samples overall (Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…In 7 of the cases where different www.nature.com/scientificreports www.nature.com/scientificreports/ predominant organisms were identified, NGS16S identified anaerobes (Table 5), consistent with the fact that anaerobes are not routinely cultured for this specimen type. Prevotella and Veillonella were frequently recovered (14/20 samples, Table 3) and represented the most abundant CRC in 6/20 samples (Table 5), consistent with previous studies 14,[25][26][27] . Anaerobes were the predominant organism in approximately one third of the samples overall (Table 5).…”
Section: Discussionsupporting
confidence: 89%
“…Howitt compared traditional microbiological cultures and 16S polymerase chain reaction analyses for the identification of preoperative airway colonization in patients undergoing lung resection. The results showed that 16S PCR analyses identify colonizing bacteria in a similar proportion of preoperative BAL samples as traditional cultures [36]. An approach based on Illumina HiSeq 16S rRNA amplicon was used by Xia et al [11], with results showing that Lactococcus lactis JCM5805 was below the detection level after the cessation of probiotics for 5 days, and they inferred that this strain could not colonize the gut; rather, the evaluation of colonization based on the 16S rRNA amplicon technology that they used is limited, for two reasons.…”
Section: Monitored Relative Abundance Changes By High-throughput Sequ...mentioning
confidence: 93%